Analisis Lama Tinggal Wisatawan di KAbupaten Kutai Kartanegara: Lama Tinggal Wisatawan - Martain (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2024)
The objective of this research is to determine the occupancy rate of tourists in Kutai KartanegaraRegency. The method used in this research is descriptive. The sampling technique that will be used is Stratified Random Sampling, which is a method of sampling by separating elements of the population into non-overlapping groups called strata. The length of stay of tourists (occupancy) in the upstream zone, who stay in accommodations, villas, and guest houses in the mentioned areas, is highest in May at 1.54 days, and lowest in January at 1.35 days. The length of stay of tourists (occupancy) in the zone staying in accommodations, villas, and guest houses in the above areas is highest in March at 1.07 days, and lowest in August at 1.02 days. Meanwhile, the highest number of stays in hotels was in May at 1.19 days, and the lowest was in January at 1.06 days. The average length of stay for tourists in the central zone is 1.11 days. The length of stay for tourists (occupancy) in the coastal zone who stay in accommodations, villas, and guest houses in the above areas is highest in May at 1.19 days, and the lowest was in March and April at 1.09 days. The length of stay of tourists (occupancy) in all zones within Kutai Kartanegara Regency who stayed in hotels, inns, villas, and guest houses is as follows: the highest length of stay for tourists was in May at 1.19 days, and the lowest in January at 1.11 days.